Increase in cannabis use may indirectly affect the health status of a freshwater species. (5th October 2016) - Parolini, Marco; Castiglioni, Sara; Magni, Stefano; Della Torre, Camilla; Binelli, Andrea
Abstract: Cannabis is the most used illicit drug worldwide and in some countries a new regulatory policy makes it legal under some restrictions. This situation could lead to a substantial increase in environmental levels of the cannabis active principle (Δ‐9‐tetrahydrocannabinol [Δ‐9‐THC]) and its main metabolite, 11‐nor‐9‐carboxy‐Δ 9 ‐tetrahydrocannabinol (THC‐COOH). Although previous studies have highlighted the toxicity of Δ‐9‐THC, the adverse effects of THC‐COOH on aquatic organisms is completely unknown, even though such effects could be more significant because the environmental concentrations of THC‐COOH are higher than those of the parent compound. The present study aimed to assess oxidative and genetic damage to the zebra mussel ( Dreissena polymorpha ) because of 14‐d exposures to 3 THC‐COOH concentrations, mimicking a current environmental situation (100 ng/L), as well as exposure to 2 possible worst‐case scenarios (500 ng/L and 1000 ng/L), because of the potential increase in THC‐COOH in surface waters. Variations in the activity of catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), and glutathione S ‐transferase (GST) were measured, as well as levels of lipid peroxidation and protein carbonyl content. Genetic injuries were investigated by single‐cell gel electrophoresis assay, DNA diffusion assay, and the micronucleus test. A significant imbalance in antioxidant defense enzymes was noted in response to the 3 tested concentrations, whereas oxidative damage was noted only at the higher one. Moreover, an increase in DNA fragmentation in zebra mussel hemocytes, but no fixed genetic damage, was found. Although the results showed that THC‐COOH toxicity was lower than that of Δ‐9‐THC, the increase in cannabis use might increase its levels in freshwaters, enhancing its hazard to bivalves and likely to the whole aquatic community. Environ Toxicol Chem 2017;36:472–479. © 2016 SETAC